Odontogenic tumors in Iran, Isfahan: A study of 260 cases - Mahsa Kowkabi; Sayed Mohammad Razavi; Negin Khosravi; Amir Arsalan Navabi (Wolters Kluwer Medknow Publications, 2012)
Background: The aim of this study was to record the relative frequency of odontogenic tumors (OTs), evaluate and analyze the epidemiological features of the lesions in patients referring to dental faculty of Isfahan and compare these data with previous studies. Materials and Methods: In this study, we reviewed the records of 6,860 lesions from 1988 to 2010 archived in the oral pathology department of dental faculty of Isfahan retrospectively and using criteria for histological typification published by the WHO in 2005. Age, sex, site and extent of tumors were analyzed. Results: Among recorded lesions 260 were OTs (3.79%). Of these, 259 were benign and just 1 was malignant. The most common lesions were ameloblastomas ( n = 95) followed by odontomas ( n = 86), odontogenic myxomas ( n = 24) and others. There were a few more female patients ( n = 133, 51.15%) than male and the mean age of patients was 27.8 years (range 1.5-80 years). The posterior of mandible was the most common site ( n = 86, 33%). Conclusion: According to accumulated data, odontogenic tumors are uncommon lesions and malignant tumors are very rare.